Remediation techniques applied for aqueous system contaminated by toxic Chromium and Nickel ion. Issue 2 (3rd April 2017) - Kumar, Ameet; Balouch, Aamna; Pathan, Ashfaque Ahmed; Mahar, Ali Muhammad; Abdullah,; Jagirani, Muhammad Saqaf; Mustafai, Faraz Ahmed; Zubair, Muneeba; Laghari, Benazir; Panah, Pirah
Abstract: Heavy metals contamination in environment is a global problem. Environment is polluted by different toxic metals due to industrial sources and anthropogenic activities. Variety of methodologies has been applied for the purification of waste water. Thus, article mainly focuses on the current developments and applicability of various wastewater treatment techniques, i.e., adsorption, membrane filtration, ion exchange, electrochemical treatment and electrocoagulation. Also, development of new adsorbents especially selective adsorbent, i.e., ion imprinted polymeric materials for selective removal and pre-concentration of toxic Nickel (II) and Chromium (VI) ions has been discussed in detail.